1976
DOI: 10.1111/j.1469-7998.1976.tb02265.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of bait and sampling intensity on trapping and estimating Wood mice, Apodemus sylvaticus

Abstract: The effects of baiting a Longworth trap with whole oats and the density of traps on an area, or sampling intensity, on trapping and estimating Wood mice were studied on two neighbouring woodland plots in November 1971. Standard capture‐mark‐recapture (CMR) methods were used for two weeks followed by five nights of removal trapping. The presence of bait significantly increased the likelihood of capturing marked and unmarked animals. By increasing the sampling intensity a greater proportion of the population was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…Heterogeneity of trap response in Wood mice has been demonstrated in these studies and this was particularly apparent when the sampling intensity was low. In the main the relative trappabiliites between members of a population did not change with time suggesting its inherent basis (Andrzejewski, Fejgin et al, 1971 ;Crowcroft & Jeffers, 1961 ;Young et al, 1952), although Gurnell (1976) has shown that the probability of capture in Wood mice in field studies improves after the initial capture.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Heterogeneity of trap response in Wood mice has been demonstrated in these studies and this was particularly apparent when the sampling intensity was low. In the main the relative trappabiliites between members of a population did not change with time suggesting its inherent basis (Andrzejewski, Fejgin et al, 1971 ;Crowcroft & Jeffers, 1961 ;Young et al, 1952), although Gurnell (1976) has shown that the probability of capture in Wood mice in field studies improves after the initial capture.…”
Section: Discussionmentioning
confidence: 94%
“…In the present studies, and in comparison with the work of Crowcroft & Jeffers (1961) on House mice, there was no evidence of territoriality (even in study 3) and it is clear that all members of a population had access to all the traps. The set-up was very different from the field situation for these wild mice and the traps probably had more significance in the laboratory as objects for exploration rather than sources of food (see Gurnell, 1976). The method has been most suitable for studying individual variation in trap response according to the number of traps available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations